Writings and Conversations - Ashford, Doug; Gruijthuijsen, Krist; Lind, Maria (Austria; Grazer Kunstverein, 2013)
This publication- the first collection of his writings and conversations- represents one of the many spaces Ashford's work occupies, and attempts to encompass the evolution of the artist's thinking over the past 25 years. Preface by Krist Gruijthuijsen, Interview by Maria Lind.
English
Keywords: N61-72 Theory. Philosophy. Aesthetics of the visual arts